1997
DOI: 10.1002/(sici)1096-8628(19971231)73:4<474::aid-ajmg18>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Regional localization of two genes for nonspecific X-linked mental retardation to Xp22.3–p22.2 (MRX49) and Xp11.3–p11.21 (MRX50)

Abstract: Two families with nonspecific X-linked mental retardation (XLMR) are presented. In the first family, MRX49, 5 male patients in 2 generations showed mild to moderate mental retardation. Two-point linkage analysis with 28 polymorphic markers, dispersed over the X-chromosome, yielded a maximal LOD score of 2.107 with markers DXS7107 and DXS8051 at theta = 0.0, localizing the MRX49 gene at Xp22.3-p22.2, between Xpter and marker DXS8022. Multipoint linkage analysis showed negative LOD values over all other regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In CLCN4 , that encodes the electrogenic chloride/proton exchanger ClC-4, 60 we discovered a protein truncating variant (p.Asp15Serfs*18, family MRX49 61 ) and four missense variants (p.Gly731Arg, family MRX15, 62 p.Leu221Val, p.Val536Met, p.Gly78Ser) (Figure 1a). ID of the affected males was variable, even within families, ranging from mild to severe.…”
Section: Resultsmentioning
confidence: 99%
“…In CLCN4 , that encodes the electrogenic chloride/proton exchanger ClC-4, 60 we discovered a protein truncating variant (p.Asp15Serfs*18, family MRX49 61 ) and four missense variants (p.Gly731Arg, family MRX15, 62 p.Leu221Val, p.Val536Met, p.Gly78Ser) (Figure 1a). ID of the affected males was variable, even within families, ranging from mild to severe.…”
Section: Resultsmentioning
confidence: 99%
“…These analyses have included a clinical and molecular study of 27 patients with deletions involving the distal short arm of the X chromosome,1 a description by Schaefer et al 3 of several patients with LD and terminal and interstitial Xp deletions,3 and a two point linkage analysis with X chromosomal markers on a family in which five males in two generations showed mild to moderate LD 8…”
Section: Discussionmentioning
confidence: 99%
“…138 139 One gene for short stature, the short stature homeobox containing gene (SHOX), 140 was also shown to be mutated or deleted in families with Leri-Weill dyschondrosteosis. 141 142 Although a putative locus for mental retardation (MRX49) has been located distal to the STS locus, 143 Tobias et al 144 reported a boy with a normal intelligence and a telomeric deletion including the STS locus as the result of a der(X)t(X;Y)(p22.31;q11.21). Clinically there is a much similarity with the case reported by De Vries et al 145 with a submicroscopic Xp22.31-pter deletion with a breakpoint just upstream of the STS locus.…”
Section: Qmentioning
confidence: 99%